IMPLEMENTASI E-COURT DALAM PENYELESAIAN PERKARA PERDATA UNTUK MEWUJUDKAN ASAS PERADILAN SEDERHANA, CEPAT, DAN BIAYA RINGAN DI PENGADILAN NEGERI SIDOARJO - Moch Alfianto Diansah; Anajeng Esri Edhi Mahanani (Gapenas Publisher, 2023)
The Sidoarjo District Court is one of the courts that has implemented or applied the Republic of Indonesia Supreme Court Regulation Number 7 of 2022. This study aims to explain the implementation of E-Court in the settlement of civil cases to realize the principle of simple, fast and low-cost justice at the Sidoarjo District Court and To analyze what are the obstacles and solutions to implementing E-Court in resolving civil cases to realize the principle of simple, fast and low-cost justice at the Sidoarjo District Court. This study uses empirical juridical research methods. Data collection was carried out by means of literature studies and interviews. Data analysis was carried out using descriptive analytical methods and using a qualitative approach. The results of the study show that the implementation of E-Court at the Sidoarjo District Court has realized the principles of simple, fast and low-cost justice, although its implementation has been hindered by the Covid-19 pandemic, E-Court has also encountered several obstacles in its implementation that have become obstacles to the implementation of E-Court. Court itself, but this has been overcome with solutions carried out by the Sidoarjo District Court